Bilateral maxillary augmentation using CAD/CAM manufactured allogenic bone blocks for restoration of congenitally missing teeth: A case report. Issue 3 (12th February 2019) - Blume, Oliver; Donkiewicz, Phil; Back, Michael; Born, Teresa
Abstract: Objective: Various biomaterials have been successfully applied in alveolar bone regeneration, however, the reconstruction of extensive osseous defects remains challenging and is often unfeasible with granular grafting materials. Several studies have outlined allogenic bone blocks as valid alternative to autologous block grafting. Clinical Considerations: In this report, we demonstrate the regeneration of two large osseous defects in the maxilla with allogenic bone blocks made from human donor bone. The bone blocks were customized using the CAD/CAM technology in order to enable the insertion of four dental implants. Conclusions: Both blocks perfectly matched the defect geometry, showed limited resorption, led to the formation of sufficient amounts of mineralized bone in both horizontal and vertical dimensions and enabled the installation of implants according to the treatment plan. The implementation of innovative technologies for individualization of allogenic bone blocks simplifies the restoration of complex and extensive osseous defects and poses great benefits for both practitioners and patients. Clinical Significance: The here presented procedure demonstrates the successful regeneration of two extensive osseous defects in a patient suffering from hypodontia using two CAD/CAM manufactured allogenic bone blocks, rendering the procedure far less invasive as compared to guided bone regeneration carried out with autologous transplants. Furthermore, to the best of our knowledge, this is the first case report that radiographically demonstrates the new formation of a cortical bone layer following block grafting with solely cancellous bone blocks.